Secondary Degeneration of White Matter After Focal Sensorimotor Cortical Ischemic Stroke in Rats - Li, Zhaoqing; Gao, Huan; Zeng, Pingmei; Jia, Yinhang; Kong, Xueqian; Xu, Kedi; Bai, Ruiliang (Frontiers in Neuroscience, 2021)
Ischemic lesions could lead to secondary degeneration in remote regions of brain. However, the spatial distribution of secondary degeneration along with its role in functional deficits is not well understood. In this study, we explored the spatial and connectivity properties of white matter (WM) secondary degeneration in a focal unilateral sensorimotor cortical ischemia rat model, using advanced microstructure imaging on a 14T MRI system. Significant axonal degeneration was observed in the ipsilateral external capsule and even remote regions including the contralesional external capsule and corpus callosum. Further fiber tractography analysis revealed that only fibers having direct axonal connections with the primary lesion exhibited significant degeneration. These results suggest that focal ischemic lesions may induce remote WM degeneration, but limited to fibers tied to the primary lesion. These “direct” fibers mainly represent perilesional, interhemispheric, and subcortical axonal connections. At last, we found the primary lesion volume might be the determinate factor of motor function deficits.